Spatial-temporal Distribution and Influencing Factors of Helicobacter pylori Infection in Chinese Mainland, 2001-2020: A Systematic Review and Meta-Analysis. Issue 5 (24th May 2022) - Lu, Tai-Liang; Zhang, Jia-Min; Li, Shao-Rong; Chen, Chao-Wu
Abstract : Background: The spatial-temporal distribution of Helicobacter pylori infection in China is poorly understood. We aimed to study the spatial-temporal distribution of H. pylori infection in Chinese mainland and to explore its influencing factors. Materials and Methods: We searched the relevant literature from 2001 to 2021 and applied meta-analysis to obtain the pooled prevalence estimates of all studies and subgroups. Then, we used the pooled prevalence as the dependent variable for the following analysis, including time series analysis, statistical mapping, spatial autocorrelation analysis, and influencing factor analysis based on generalized additive model and panel data model. Results: A total of 726 articles and 3, 407, 392 people were included. The pooled prevalence was 43.7% (95% confidence interval: 42.7%–44.8%). The prevalence decreased in the past 20 years, with high in the eastern and western regions and low in the central region. Qinghai Tibet Plateau and Guizhou Plateau were the high incidence areas of this disease. The intake of vegetable oil, aquatic products, meat, milk, per capita gross domestic product, and annual average humidity were significantly correlated with H. pylori . Conclusions: The prevalence of H. pylori is decreasing in Chinese mainland, but still high in underdeveloped areas. Appropriate strategies for the prevention need greater attention.